2016
DOI: 10.3168/jds.2016-11172
|View full text |Cite
|
Sign up to set email alerts
|

Influence of raw milk quality on processed dairy products: How do raw milk quality test results relate to product quality and yield?

Abstract: This article provides an overview of the influence of raw milk quality on the quality of processed dairy products and offers a perspective on the merits of investing in quality. Dairy farmers are frequently offered monetary premium incentives to provide high-quality milk to processors. These incentives are most often based on raw milk somatic cell and bacteria count levels well below the regulatory public health-based limits. Justification for these incentive payments can be based on improved processed product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 85 publications
(141 reference statements)
3
106
0
16
Order By: Relevance
“…When a milk producing animal suffers from mastitis, the produced milk will have elevated levels of somatic cells and microbial enzymes that can survive pasteurization (Li et al., ; Li, Richoux, Boutinaud, Martin, & Gagnaire, ). High somatic cell counts in initial raw milk can result in low quality dairy products since they occur as an important source of different enzymatic enzymes that could influence the dairy manufacture processes and consequently products quality (Li et al., ; Murphy, Martin, Barbano, & Wiedmann, ; Paixão, Abreu, Richert, & Ruegg, ). The legal threshold of somatic cell counts of milk in dairy industries of the European Union is 4 × 10 5 cells/mL (FAO Legal Office, ).…”
Section: Resultsmentioning
confidence: 99%
“…When a milk producing animal suffers from mastitis, the produced milk will have elevated levels of somatic cells and microbial enzymes that can survive pasteurization (Li et al., ; Li, Richoux, Boutinaud, Martin, & Gagnaire, ). High somatic cell counts in initial raw milk can result in low quality dairy products since they occur as an important source of different enzymatic enzymes that could influence the dairy manufacture processes and consequently products quality (Li et al., ; Murphy, Martin, Barbano, & Wiedmann, ; Paixão, Abreu, Richert, & Ruegg, ). The legal threshold of somatic cell counts of milk in dairy industries of the European Union is 4 × 10 5 cells/mL (FAO Legal Office, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the interpretation is different, because the increase in SCC gives a negative economic value, which leads the companies to penalize farmers that supply milk with high SCC. Their increase in milk reflected in lower yield in manufactured dairy products and lower shelf life of these products (Murphy et al, 2016). Another relevant aspect regarding SCC is related to public health issues, because, according to Kunda et al (2016) as SCC increases the likelihood of antibiotic residues in milk being found also increases.…”
Section: Labormentioning
confidence: 99%
“…According to Murphy et al (2016), the SCC increase also causes decrease in milk production and its components, which could contribute to the reduction of the annual profit of the herd. Clinical and subclinical mastitis are related to increased production of SCC in milk (Koeck et al, 2012) and are also causes of involuntary culling of dairy cows (Roelofs et al, 2010) thereby affecting other traits measured in the indices.…”
Section: Labormentioning
confidence: 99%
“…This author further stated that milk composition traits determine the quality of milk produced by dairy cows and have economic value since dairy producers are paid premium value for milk of higher than average quality or composition. Milk component levels and characteristics are important factors that have a significant effect on dairy product quality and yield [4].…”
Section: Introductionmentioning
confidence: 99%